Rejection-associated Phenotype of De Novo Thrombotic Microangiopathy Represents a Risk for Premature Graft Loss. Issue 11 (22nd October 2021) - Petr, Vojtech; Hruba, Petra; Kollar, Marek; Krejci, Karel; Safranek, Roman; Stepankova, Sona; Dedochova, Jarmila; Machova, Jana; Zieg, Jakub; Slatinska, Janka; Pokorna, Eva; Viklicky, Ondrej
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Thrombotic microangiopathy (TMA) significantly affects kidney graft survival, but its pathophysiology remains poorly understood. Methods: In this multicenter, retrospective, case–control paired study designed to control for donor-associated risks, we assessed the recipients' risk factors for de novo TMA development and its effects on graft survival. The study group consists of patients with TMA found in case biopsies from 2000 to 2019 (n = 93), and the control group consists of recipients of paired kidney grafts (n = 93). Graft follow-up was initiated at the time of TMA diagnosis and at the same time in the corresponding paired kidney graft. Results: The TMA group displayed higher peak panel-reactive antibodies, more frequent retransplantation status, and longer cold ischemia time in univariable analysis. In the multivariable regression model, longer cold ischemia times (odds ratio, 1.18; 95% confidence interval [CI], 1.01-1.39; P = 0.043) and higher peak pretransplant panel-reactive antibodies (odds ratio, 1.03; 95% CI, 1.01-1.06; P = 0.005) were found to be associated with increased risk of de novo TMA. The risk of graft failure was higher in the TMA group at 5 y (hazard ratio [HR], 3.99; 95% CI, 2.04-7.84; P < 0.0001). Concomitant rejection significantly affected graft prognosis at 5 y (HR, 6.36; 95% CI, 2.92-13.87; P < 0.001). De novo TMA associated with the active antibody-mediated rejection was associated with higher risk of graft failure at 5 y (HR, 3.43; 95% CI, 1.69-6.98; P < 0.001) compared with other TMA. Conclusions: Longer cold ischemia and allosensitization play a role in de novo TMA development, whereas TMA as a part of active antibody-mediated rejection was associated with the highest risk for premature graft loss.